Pengaruh Pemahaman Akuntansi, Sistem Informasi Akuntansi, dan Fungsi Dewan Pengawas terhadap Kualitas Laporan Keuangan pada Badan Usaha Milik Desa di Kecamatan Buleleng - Kadek Diana Dwiyanti; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2024)
This study aims to partially examine the effect of accounting understanding, accounting information systems, and supervisory board functions on the quality of financial statements of Village-Owned Enterprises in Buleleng District. This research was included in a quantitative approach with multiple linear regression analysis techniques. The population used in this study was 12 Village-Owned Enterprises in Buleleng District. By using purposive sampling techniques, there were a total of 80 respondents. The data collection method used questionnaires distributed to 80 people, but the number of questionnaires that returned and could be processed was 67 questionnaires. Data processed using SPSS 26 for Windows includes descriptive statistics, instrument tests, classical assumption tests, and hypothesis tests. The results showed that: (1) accounting understanding has a positive and significant effect on the quality of financial statements; (2) accounting information system has a positive and significant effect on the quality of financial statements; (3) the function of the supervisory board does not affect the quality of financial statements.